New Software Performance with Balanced Score Card Assessment: Case Study at LPGI Jakarta - Djojo, Brata Wibawa (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
Implementation of information technology (IT), especially new software applications, needs to be evaluated for its impact to organizationâ€™s business performance related to its strategic goal. The measurement and evaluation of a new software implementation impact in LPGI Jakarta uses Balanced Scorecard (BSC) analysis by making comparison of three-year data. The analysis involves four perspectives of BSC: (1) Financial aspect with the growth of gross premium written (GPW), net premium written (NPW), underwriting profit; (2) internal business aspect: the frequency of policy issued and the average production per policy; (3) people or learning and growth which consists of human error and system error; (4) customer aspect with external endorsement and renewal ratio. This research measures and evaluates for the impact of the implementation of a new software application to the new business performance as Marginal and Fair contribution.Â  At the end of this paper the writer suggests LPGI Jakarta to increase the sales activities to reach the target which is related directly to financial aspect and internal business process aspect.